1993
DOI: 10.1093/infdis/168.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Markers of Human Immunodeficiency Virus Type 1 in Cerebrospinal Fluid

Abstract: As part of a longitudinal study, 265 cerebrospinal fluid (CSF) specimens from 204 human immunodeficiency virus type 1 (HIV-1)-seropositive subjects and 43 seronegative controls were evaluated. Of the 204 seropositive persons, 78 (38%) had > or = 1 CSF culture positive for HIV-1; the probability of being culture positive increased as the number of CSF samples obtained increased (P = .0018). Significantly correlated with culture positivity were elevations in CSF protein level (P = .014) and CSF white blood cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 34 publications
4
12
0
3
Order By: Relevance
“…The virus in the CSF of the subjects examined by Ellis et al (1997) was, however, cell-free virus. A previous study also noted that HIV-1 isolated from the CSF was found in the supernatant rather than in the cellular fraction (Spector et al, 1993) suggesting that the CSF/plasma relationship is attributable to cellfree virus, and might be indirectly related to lymphocytic pleocytosis.…”
Section: Discussionmentioning
confidence: 90%
“…The virus in the CSF of the subjects examined by Ellis et al (1997) was, however, cell-free virus. A previous study also noted that HIV-1 isolated from the CSF was found in the supernatant rather than in the cellular fraction (Spector et al, 1993) suggesting that the CSF/plasma relationship is attributable to cellfree virus, and might be indirectly related to lymphocytic pleocytosis.…”
Section: Discussionmentioning
confidence: 90%
“…Western blot analyses also indicated that clinically available inhibitors of HMG-coenzyme A reductase, atorvastatin and simvastatin, inhibited HIV-1-induced release of Hsp70 from neurons. (78,87). Several studies have shown that there is a potential interaction between alcohol and several other drugs of abuse and HIV-1 infection (26,30,51).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Expomentioning
confidence: 99%
“…HIV-1 enters the CNS early in the course of disease (Resnick et al, 1988;Spector et al, 1993) and establishes productive infection in the brain, detectable in perivascular macrophages and microglia. Despite the absence of productive infection of neurons, HIV-1 infection is associated with neuronal loss in distinct regions of the brain, including the frontal cortex, substantia nigra, cerebellum, and striatum (Everall et al, 1993).…”
Section: Introductionmentioning
confidence: 99%